A, The Artikel Pemberdayaan Masyarakat Dalam Mengembangkan Wisata Pantai Tabanio Kabupaten Tanah Laut Kalimantan Selatan - Rizqita Shelin Ayudia; Tomi Oktavianor (Public Inspiration : Jurnal Administrasi Publik, 2025)
Community-based tourism is a tourism management concept that prioritizes active community participation with the aim of providing welfare for them while maintaining environmental quality, and protecting their social and cultural life. The purpose of this research is to conduct an analysis of community empowerment in developing Tabanio beach tourism in Tanah Laut Regency, South Kalimantan. The type of research used is descriptive qualitative with in-depth interview techniques. The research instrument is the researcher with informants consisting of; Head of Tourism Office, Village Head, Village community, Pokdarwis Tabanio Beach, and visitors. The results of the study indicate that; community empowerment in developing tourism in Tabanio Beach at 1) the awareness and behavior formation stage towards conscious behavior and requiring increased self-capacity has not been implemented properly or optimally, 2) the transformation stage of abilities in the form of knowledge insight, skills, basic skills has not been implemented properly or optimally, 3) the stage of increasing intellectual abilities, skills, skills has never been implemented. Thus, community empowerment in developing Tabanio beach tourism in Tanah Laut Regency, South Kalimantan has not been implemented optimally. Therefore, the role of related parties is further enhanced, so that community empowerment in developing Tabanio Beach tourism in Tanah Laut Regency can run well and optimally.